Possibilidades do uso de práticas experimentais e da teoria da objetivação em sala de aula on-line para o ensino e aprendizagem de fungos - Frenham, Karina Franco (2021)
The present research was developed with the general objective of analyzing a teaching and learning proposal with tasks that include experimental practices on fungi, which was based on the Theory of Objectification, for teaching Science in an online classroom, elementary level II. This proposal was readjusted for the development of Science lessons in the online classroom for the period when in-person classes in schools were suspended due to the COVID-19 pandemic. The Theory of Objectification - TO was adopted as a theoretical and methodological reference because it is an educational theory inspired by dialectical materialism and sociocultural theories, which considers teaching and learning as a single process that involves the objectification process (materialization of knowledge) and the subjectification process (transformation of Being). The proposal consisted in the planning and the execution of lessons based on the development of five teaching and learning activities (TLA), in which the first one was about living beings and the other four were about fungi, with their respective tasks, consisting of several actions, among which, in two of them, experimental practices were proposed and carried out with the use of experimental artifacts. This is a qualitative research whose methodological unit of analysis is the activity (joint labor) between teachers and students. The classes, based on joint labor, were developed from May to June 2021. The data was obtained through recordings of the online meetings, the participants' productions (task sheets), opinions, diagnostic questions, and field notes. Based on the TO conception, we analyzed the joint work of four 7th grade students from a municipal school in Campo Grande/MS, through the relevant episodes extracted from the interactions between the students and the researcher teacher. The results showed evidence of the students' encounter with the knowledge related to the theme fungi (objectification process), among which we highlighted the characteristics of fungi, the alcoholic fermentation process and the importance of fungi for humans and the environment. We also observed changes in the students' behavior (process of subjectification) during the joint work as they reflected on the problems caused by mycosis and other fungal contaminations. Furthermore, we observed during the group interactions that they practiced community ethics when they took responsibility and commitment in performing the tasks and showed care and respect for others, helping their colleagues to understand the knowledge about fungi. The performance of experimental practices with the use of the experimental cultural artifact, even though it was done in the remote way, made it possible to investigate and discuss the action of fungi (alcoholic fermentation and contamination of homemade and industrialized bread). The proposal of the online teaching and learning based on the TO presents itself as an alternative to break with individualistic teaching, doing so through joint labor by practicing community ethics.